Mapping the Internal Supply Chain Management for Multicultural Initiatives in Regional Higher Institutions - Zhukova, Tatiana; Bogoslovskiy, Vladimir; Dobudko, Tatiana; Pisareva, Svetlana; Sevenyuk, Svetlana; Vershinina, Lidiya (International Journal of Supply Chain Management, 2018)
Nowadays scientists from different countries and regions of the countries speak about current issues on the problem of multicultural experiences policy in education in regional higher institutions. Moreover they believe that together that is possible to set the aims and the further multicultural initiatives for the future of the world regional and personal cultures challenges. Identifying and understanding the Internal Supply Chain (ISC) Frame work of an organization is an effective management tool. The study is an exploratory one mainly because of scanty literature on supply chain management in the education sector. Thus, they give the ideas of further foundation of multicultural initiatives in education, to set the stage for open communication between educational and cultural organizations of different regions of the countries. In this paper we highlighted the importance of multicultural initiatives development in regional higher institution in Russia. Focusing on three specific educational contexts (multicultural education in every region, comparative approach to multicultural competence development in regional higher institutions, curriculum design within higher institutions in multicultural regions), they provide their view on the problem that educators can relate to and apply to their own regional higher institutions. It was recommended that for efficient operation of the Internal Supply Chain (ISC) in regional higher institution in Russia, there needed to be optimal information flow as well as materials (Human, Financial and Physical resources) flow throughout the university.